Pembinaan Keterampilan Menulis Huruf Hijaiyah bagi Anak Usia Sekolah Dasar melalui Pembelajaran Kaligrafi Arab di Majlis Ta’lim Nurul Huda Desa Cirangkong - Ghina, Ghina Agniya Suhulah; Oktriawan, Wawan; Wulandari, Dyah (Institut Agama Islam Hamzanwadi NW Pancor, 2024)
Community service activities aim to provide skills development in writing hijaiyah letters, this training is carried out at the Majlis Ta'lim Nurul Huda, Cirangkong Village, where children need additional hours outside of school by studying at the Majlis Ta'lim, especially additionally in terms of Islamic Religious Education . The method used in this service program is the PAR (Participatory Action Research) method. This program is more focused on developing skills in writing hijaiyah letters (learning calligraphy) for school-aged children. The skill of writing hijaiyah or Al-Qur'an letters is directed at how to write short letters in the Al-Qur'an according to the rules of good and correct Arabic writing. This program has continuity with the TPQ programs found in Cirangkong village councils. In Cirangkong Village, the majority are only children and parents, so the only benchmarks for observers are children and mothers. Based on empirical facts and evaluations that have been carried out, it shows that Arabic or Al-Quran writing skills for students in Cirangkong Village, Cibatu District are still in the sufficient category. This sufficient category is given with various considerations, including the results of evaluations of both writing and pronunciation, in addition, this category is also based on various observation results in coaching processes. Students have the technical ability to write hijaiyah letters properly and correctly according to the writing rules independently. However, students still find it difficult to write these letters in cursive form, because Arabic letters will change their writing form when they are in different positions.